2018
DOI: 10.1007/s13361-018-1985-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanoparticles and Graphene Nanosheets as MALDI Matrices in Glycomics: a New Approach to Improve Glycan Profiling in Biological Samples

Abstract: Glycomics continues to be a highly dynamic and interesting research area due to the need to comprehensively understand the biological attributes of glycosylation in many important biological functions such as the immune response, cell development, cell differentiation/adhesion, and host-pathogen interactions. Although matrix-assisted laser desorption ionization (MALDI) mass spectrometry (MS) has proven to be suitable for glycomic profiling studies, there is a need for improved sensitivity in the detection of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
(46 reference statements)
2
36
0
Order By: Relevance
“…S1b) indicated that CNPs@Fe 3 O 4 NCs have a broad absorption peak from 250 nm to 375 nm which corresponds to a π−π* transition of aromatic sp 2 carbon domains. As it was shown in our previous work [26], Raman spectra also confirmed π-conjugation structures of CNPs. Comparing CNPs and Fe 3 O 4 NPs, the UV−Vis data verified higher molar absorptivity of CNPs@Fe 3 O 4 NCs, at the MALDI laser radiation wavelength (355 nm).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…S1b) indicated that CNPs@Fe 3 O 4 NCs have a broad absorption peak from 250 nm to 375 nm which corresponds to a π−π* transition of aromatic sp 2 carbon domains. As it was shown in our previous work [26], Raman spectra also confirmed π-conjugation structures of CNPs. Comparing CNPs and Fe 3 O 4 NPs, the UV−Vis data verified higher molar absorptivity of CNPs@Fe 3 O 4 NCs, at the MALDI laser radiation wavelength (355 nm).…”
Section: Resultssupporting
confidence: 88%
“…1a), resulting in poor shot-to-shot reproducibility in MALDI analyses [26, 39, 40]. Although crystallization could be improved via recrystallization using methanol, still small crystals formed near the rim (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations